İNTRAUTERİN GELİŞME GERİLİĞİ OLGULARINDA UTERİN ARTER DOPPLER BULGULARININ PLASENTA YATAK BİYOPSİSİ HİSTOLOJİSİ İLE İLİŞKİSİ - SOMUNKIRAN, Aslı; MADAZLI, Rıza; CALAY, Zerrin; İlvan, Şennur; KÖRBEYLİ, Begüm; ŞİMŞEK, Yavuz (Cerrahpaşa Medical Journal, 2014)
Background and Design.- The aim of this study was to determine the relationship between placental bed biopsy findings and uterine artery doppler flow parameters in intrauterine growth retardation(IUGR). We tested the hypotesis that Doppler velocimetry of the uterine artery in cases of fetal intrauterine growth retardation can reflect the presence of vascular maladaptation to pregnancy. Uterine artery doppler velocimetry was obtained in 47 consecutive pregnancies with IUGR and 26 unevetful control pregnancies. Abnormal uterine doppler velocimetry was defined as an average of S/D ratio>2.6 and distolic notching. In cases of C/S, after removal of the placenta, a placental bed biopsy, containing the uteroplacental vessels of the decidual and inner myometrial layer, was taken. The bed biopsies were examined for uteroplacental vascular pathological features. Results.- The physiological changes in the spiral arteries was seen in all (100%) AGA fetuses, in 45% of IUGG cases. The pathologicall changes in the placental bed biopsy was found %0 for controls, % 16 for growthrestricted fetuses with normal uterine artery Doppler, and % 82 for IUGR fetuses with abnormal uterine artery Doppler. Conclusion.- These data suggest that Doppler velocimetry of the uterine arteries is predictive of vascular lesions in growth-restricted fetuses.